Status of ratification of Agreements negotiated under the auspices of the Arctic Council. - Arctic Council Secretariat (ACS) (Arctic Council Secretariat, 2015)
Document listing the status of ratification of Agreements negotiated under the auspices of the Arctic Council. Submitted by the Arctic Council Secretariat to the Arctic Council's Senior Arctic Officials meeting in Anchorage, USA, October 21-22 2015.